Particle Dynamics around Weakly Magnetized Reissner-Nordström Black Hole - Bushra Majeed; Mubasher Jamil; Saqib Hussain (Advances in High Energy Physics)
Considering the geometry of Reissner-Nordström (RN) black hole immersed in magnetic field, we have studied the dynamics of neutral and charged particles. A collision of particles in the inner stable circular orbit is considered and the conditions for the escape of colliding particles from the vicinity of black hole are given. The trajectories of the escaping particle are discussed. Also, the velocity required for this escape is calculated. It is observed that there is more than one stable region if magnetic field is present in the accretion disk of black hole, so the stability of ISCO increases in the presence of magnetic field. Effect of magnetic field on the angular motion of neutral and charged particles is observed graphically.